Sepsis alters NK cell transcriptional programs for stress, actin remodeling, and intracellular trafficking [data] - Lindner, Holger A.; Torre, Carolina de la; Velásquez, Sonia Y.; Schulte, Jutta; Sticht, Carsten; Thiel, Manfred; Coulibaly, Anna (Universität, 2026)
Background: Natural killer (NK) cells exert cytotoxicity against transformed and infected cells. In human sepsis, a suppressive NK cell receptor signature and defective effector molecule expression have been described. However, the transcriptional mechanisms underlying this phenotype remain poorly defined. Methods: We analyzed microarray-based transcriptomic profiles of isolated peripheral NK cells from patients with sepsis, systemic inflammatory response syndrome (SIRS), and presurgical controls. Enrichment analyses of canonical pathways, biological processes, and cellular compartments were performed. Differential gene expression was validated in an independent cohort using a multiplex branched-DNA assay. Functional STAT phosphorylation responses ex vivo and proliferation marker expression were assessed by flow cytometry in independent patient samples. Results: NK cells from sepsis patients displayed transcriptional signatures indicative of DNA replication stress, ER stress, altered cytoskeletal dynamics and vesicle trafficking. Despite enrichment of proliferation-associated transcriptional programs, NK cells showed no increase in Ki-67 expression, indicating impaired proliferative activity. In contrast, NK cells from SIRS patients exhibited downregulation of immune signaling pathways. Conclusion: This study identifies early stress-associated transcriptional programs and impaired subcellular organization in circulating NK cells during sepsis. Dysregulated DNA replication and ER stress responses, along with altered vesicle trafficking linked to impaired small GTPase signaling, may contribute to NK cell dysfunction in sepsis and may inform the development of NK cell-based immunotherapeutic strategies in critical illness.
Gefördert durch: Klaus Tschira Foundation, Germany: 00.0277.2015
Gesehen am 04.02.2026
Keywords: Forschungsdaten; Datenbank